2012
DOI: 10.21432/t2b88w
|View full text |Cite
|
Sign up to set email alerts
|

Student Satisfaction with Blended and Online Courses Based on Personality Type / Niveau de satisfaction des étudiants dans les cours hybrides et en ligne basé sur le type de personnalité

Abstract: The purpose of the study was to investigate differences in perceived student satisfaction in blended and online learning environments based on personality type. A total of 72 graduate students enrolled in blended and online courses at two research universities in the United States completed an abbreviated online version of the Myers-Briggs Type Indicator (MBTI®) and an online student satisfaction questionnaire. Overall, results indicate participants were satisfied with courses delivered in both environments. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
(25 reference statements)
0
15
1
Order By: Relevance
“…Meredith (2011) studied the relationship between the personality types of students and their success in online courses and found that personality is an influencing factor for the success of students in terms of final course grade and retention rate. Bolliger and Erichsen (2013) investigated the differences in learners' satisfaction in online and blended learning based on their personality type and found that personality type influenced learners' satisfaction in both conditions. In another study, Kelly and Schorger (2002) used the Myers-Briggs Type Indicator and the Student Perceptions of Online Learning to explore the relationship between personality traits and perceptions towards online learning.…”
Section: Personality and Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Meredith (2011) studied the relationship between the personality types of students and their success in online courses and found that personality is an influencing factor for the success of students in terms of final course grade and retention rate. Bolliger and Erichsen (2013) investigated the differences in learners' satisfaction in online and blended learning based on their personality type and found that personality type influenced learners' satisfaction in both conditions. In another study, Kelly and Schorger (2002) used the Myers-Briggs Type Indicator and the Student Perceptions of Online Learning to explore the relationship between personality traits and perceptions towards online learning.…”
Section: Personality and Online Learningmentioning
confidence: 99%
“…They found a significant difference in the retention rate between the two groups. In order to engage learners, it is very important to understand individual differences among the learners involved (Bolliger & Erichsen, 2013;Cela-Ranilla, Gisbert, & de Oliveira, 2011;Chamorro-Premuzic & Furnham, 2005;O'Connor & Paunonen, 2007). Bolliger and Erichsen mentioned that personality type affects students' preferences towards educational settings.…”
Section: Introductionmentioning
confidence: 99%
“…Al Ghamdi (2017) stated that using up-to-date e-learning features can reduce the feeling of separation between students and lecturers within the distance education environment, can promote effective communication, and can improve the learning years and become one of the major goals of all educational institutions" (p. 3802). Bolliger and Erichsen (2013) defined student satisfaction as "the learner's perceived value of their educational experiences in an educational setting" (p. 5). It is one of the crucial factors that shape the success of the learning process, whether it is traditional or online.…”
Section: Student Satisfaction: An Overviewmentioning
confidence: 99%
“…Also, parties are recommended to make decisions as 'thinkers' where judgements are based on logic and objective analysis of the facts, rather than 'feelers' who make decisions by assessing their values and very subjective [58] as this affects the relational dimensions of information. In dealing with external project actors, parties are recommended to be 'judgers' -structured, plan, and organise information, instead of perceivers who do not plan are tentative and open-minded [12] to reduce vulnerability to information security. Psychologically, the above behaviours are observable cues from traits and attitudes of individuals [2].…”
Section: Developing the Ir Frameworkmentioning
confidence: 99%